Case report of unilateral abducens nerve paresis: A common sign with an uncommon etiology - Valerie Menezes; Ramona Menezes (TNOA Journal of Ophthalmic Science and Research, 2022)
Sixth nerve paresis is a rare presentation of intracranial aneurysms. We report an uncommon case of unilateral sixth nerve paresis in a young adult as the main presenting feature of an intracavernous aneurysm. The patient presented with pain and double vision in the right eye for 1 month. Computerized Tomography scan brain done elsewhere was normal. Examination showed right sixth nerve paresis with sensory loss in the first and second divisions of the trigeminal nerve. We suspected a cavernous sinus lesion and conveyed the same to the radiologist who therefore did additional and appropriate imaging, which revealed an intracavernous carotid aneurysm. This case is unique as to the best of our knowledge, it is the first case of its kind reported from India.